STUDI IMPLEMENTASI STANDAR PROSES DALAM PEMBELAJARAN KURIKULUM 2013 PADA GURU SEKOLAH DASAR KABUPATEN MELAWI - Ason, Ason; Saputro, Eko Fery Haryadi (STKIP Melawi, 2019)
Abstract: This study aims to determine the percentage of the level of teacher competence in implementing the 2013 curriculum, especially on the standard processes that include learning planning, the implementation of the learning process and the assessment of the learning process. This research was conducted at the Melawi Regency Elementary School, by taking 6 research samples from 258 elementary schools in Melawi Regency. This research was conducted for 3 months, from February to April 2019. The study used a descriptive qualitative approach with research subjects being teachers in several elementary schools in Melawi Regency. Data collection through a questionnaire that measures the level of competence of each teacher in implementing K-13, with the 5th sakala that is Very Appropriate (91-100%); Appropriate (81-90%), Fairly Adjusted (71-80%), Less Adjusted (61-70%) and Unsuitable (60% ?). The results of the study were analyzed by interactive analysis with the steps of reduction, presentation and verification. The results of this study indicate that, the competence of teachers in planning 2013 curriculum-based learning is as follows: those included in the good category amounted to 14%, the categories were quite 61%, and the category lacked 25%. While the level of teacher competence in implementing the 2013 Curriculum-based learning process, the good category is 18%, the category is 75%, and the category is less 7%. For the competence of teachers in carrying out 2013 curriculum-based learning evaluations, namely the good category 25%, the category is 68%, and the category is less 7%. Thus it can be concluded that the average level of competence of Melawi Regency Elementary School teachers in understanding the 2013 curriculum, which includes learning planning, carrying out the learning process and conducting assessment of the learning process are good categories 19%, 68% sufficient and less 13%.Keywords: Process Standards, Elementary School Teacher Learning Abstrak: Penelitian ini bertujuan untuk mengetahui prosentase tingkat kompetensi guru dalam mengimplementasikan Kurikulum 2013 khususnya pada standar proses yang meliputi perencanaan pembelajaran, pelaksanaan proses pembelajaran dan penilaian proses pembelajaran. Penelitian ini dilaksanakan di Sekolah Dasar Kabupaten Melawi, dengan mengambil 6 sampel penelitian dari 258 SD yang ada di Kabupaten Melawi. Penelitian ini dilaksanakan selama 3 bulan yakni dari bulan Februari sampai dengan bulan April 2019. Penelitian menggunakan pendekatan kualitatif deskriptif dengan subyek penelitian adalah guru di beberapa SD di Kabupaten Melawi. Pengumpulan data melalui angket yang mengukur tingkat kompetensi guru masing-masing dalam mengimplementasikan K-13, dengan sakala 5 yakni Sangat Sesuai (91-100%); Sesuai (81-90%), Cukup Sesuai (71-80%), Kurang Sesuai (61-70%) dan Tidak Sesuai (60% ?). Data dianalisis dengan analisis interaktif dengan langkah-langkah reduksi data, penyajian data dan verifikasi data. Hasil penelitian ini menunjukkan bahwa, kompetensi guru dalam merencanakan pembelajaran berbasis Kurikulum 2013 adalah sebagai berikut: yang masuk dalam kategori baik sebesar 14%, katagori cukup 61%, dan kategori kurang 25%. Sedangkan tingkat kompetensi guru dalam melaksanakan proses pembelajaran berbasis Kurikulum 2013 , kategori baik 18%, katagori cukup 75%, dan kategori kurang 7%. Untuk kompetensi guru dalam melaksanakan evaluasi pembelajaran berbasis Kurikulum 2013 yaitu kategori baik 25%, katagori cukup 68%, dan kategori kurang 7%.Kata Kunci: Standar Proses, Pembelajaran Guru Sekolah Dasar